VHL c.505 T>C mutation confers a high age related penetrance but no increased overall mortality. Issue 8 (1st August 2001) - Bender, Bernhard U; Eng, Charis; Olschewski, Manfred; Berger, Dietmar P; Laubenberger, Jörg; Altehöfer, Carsten; Kirste, Günter; Orszagh, Miro; van Velthoven, Vera; Miosczka, Henning; Schmidt, Dieter; Neumann, Hartmut P H
Abstract : BACKGROUND: Germline mutations of the VHL gene cause von Hippel-Lindau syndrome (VHL). In southern Germany, a specific mutation in this gene, c.505 T>C, is one of the most frequent alterations owing to a founder effect. METHODS: This study was conducted to evaluate morbidity, specific clinical risk profile, and mortality among a series of VHL c.505 T/C mutation carriers. A total of 125 eligible subjects carrying VHL c.505 T/C underwent ophthalmoscopy and gadolinium enhanced magnetic resonance imaging of the brain, the spinal cord, and the abdomen. Age related penetrance, morbidity, and mortality were assessed. RESULTS: Frequently observed lesions were phaeochromocytoma (47%), retinal angiomas (36%), haemangioblastoma of the spine (36%), and haemangioblastoma of the brain (16%). Four patients developed renal cell carcinoma. VHL was symptomatic in 47% of subjects; 30% were asymptomatic despite the presence of at least one VHL related tumour and 23% of the carriers had no detectable VHL lesion. Of the 19 patients who had died (15%), 10 died of symptomatic VHL lesions. Overall penetrance by cumulative incidence functions is estimated at 48% by 35 years and 88% by 70 years. In contrast to the only existing published report based on patients with presumably unselected VHL germline mutations, the mortality rate for c.505 T/C mutation carriers is comparable to that of the general population of Germany. CONCLUSIONS: Our results are an important example that a specific genotype, at least in the case of VHL c.505 T/C, can favourably impact on mortality despite a high age related penetrance. Our study also indirectly provides objective data which might be useful to the life and health insurance industry; it would appear that c.505 T>C mutation positive subjects have similar disease specific mortality to that of the general population owing to a combination of phenotype and timely detection of mutation carrier status followed by aggressive clinical screening and, if necessary, treatment.